The Role of Integrated Mashgulotarnig in the Development of the Process of Cognition of Preschool Children - S.Irisova. (Genius Publishing Group, 2023)
The article shows the methods of organizing integrated learning in preschool educational organizations, as well as the formation of creative skills in pupils of activity centers.
Keywords: integration; activity centers; training; educational game